Effects of Alanine Methyl Ester Hydrochlorides on Thermal Behaviour of Biodegradable Poly(L-lactic Acid) - Cai, Yan-Hua; Xu, Qiang; Tang, Ying; Luo, Wen; Zhang, Shen-Wei; Hao, Hai-Tao (Asian Journal of Chemistry, 2012)
Alanine methyl ester hydrochlorides (AMEH) was synthesized to improve the crystallization of poly(L-lactic acid) (PLLA) and PLLA/AMEH was prepared by melt blending and hot-press forming process. The thermal behaviour of PLLA/AMEH was investigated by DSC. Non-isothermal crystallization showed that alanine methyl ester hydrochloride made the melt crystallization peak become much sharper in the cooling process and the crystallization enthalpy increases from 1.379 to 9.941 J g-1 with the addition of 2 % alanine methyl ester hydrochloride at a cooling rate of 1 ºC/min from melt. The melting behaviour of PLLA/2 % AMEH after at different crystallization temperature for 1 h confirmed that double-melting peak of PLLA/2 % AMEH resulted from melting-recrystallization, However, the high-temperature melting peak becomes smaller with increasing of crystallization temperature.